Optical properties of Ta2O5 thin films deposited using the spin coating process - Ghodsi, Farhad E.; Tepehan, Fatma Z.; Tepehan, Galip G. (Elsevier BV, 1997)
Abstract Optical properties of tantalum pentoxide thin films have been investigated. The films were prepared by the sol-gel method using the spin coating process. Refractive index and absorption coefficient of the films have been calculated with respect to spinning velocity and number of coating layers from optical transmission measurement in the range 200-1100 nm. Forbidden bandgaps of the films are found to be 3.75 ± 0.12 eV and independent of the film thickness and spin rate.